The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1177/014920639402000401
|View full text |Cite
|
Sign up to set email alerts
|

Pressure, Opportunity and Predisposition: A Multivariate Model of Corporate Illegality

Abstract: Corporate illegality researchers often maintain that wrongdoing occurs when factors pressure a firm to behave illegally, leading managers to make a rational decision to commit wrongdoing. Yet, corporate illegality results also from conditions of opportunity and predisposition, and it may be an unintended outcome of corporate actions. A multivariate model of corporate illegality is proposed, in which situational factors-conditions of pressure, opportunity, or predisposition-lead to unintentional and intentional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
2
33

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(171 citation statements)
references
References 16 publications
10
126
2
33
Order By: Relevance
“…Along these lines, Alexander and Cohen (1996) found that firms with poor performance were more likely to commit environmental crimes. Research on corporate corruption also supports the idea that poor performance is often an antecedent to corrupt behaviors (Baucus, 1994). However, the impact of performance is likely to depend on the stock-based incentive situation.…”
Section: Contingency Of Stock-based Incentivesmentioning
confidence: 88%
“…Along these lines, Alexander and Cohen (1996) found that firms with poor performance were more likely to commit environmental crimes. Research on corporate corruption also supports the idea that poor performance is often an antecedent to corrupt behaviors (Baucus, 1994). However, the impact of performance is likely to depend on the stock-based incentive situation.…”
Section: Contingency Of Stock-based Incentivesmentioning
confidence: 88%
“…Many studies have analyzed in depth a single incidence of corporate misconduct (e.g. Baucus ; Greve et al . ; Mishina et al .…”
Section: Discussionmentioning
confidence: 99%
“…Though investigators in this domain have traditionally grouped crimes committed against organizations together with crimes committed for them (Sutherland, 1940), scholars have more recently been careful to distinguish between the two (Pinto, Leana, & Pil, 2008). Additionally, some organizational crime experts (e.g, Baucus, 1994) dichotomize acts committed for organizations according to intentionality. While some organizationally beneficial legal violations are accidental and without awareness (e.g., failing to comply out of ignorance), others are deliberate (e.g., intentionally dumping bilge waste to save money).…”
Section: Workplace Deviance As Dcbmentioning
confidence: 99%
“…In the wake of regular and explicit media coverage of incidents like the ones described above, scholars have proposed several related but distinct constructs that account for pro-organizational behaviour that harms stakeholders in unreasonable and unnecessary ways. These theoretical frameworks, however, tend to only address a subset of this type of problematic behaviour (e.g., violations of law; Baucus, 1994) or account for its causes and consequences only at one level of analysis (e.g., at the individual level of analysis; Umphress & Bingham, 2011). Consequently, we lack a cohesive, integrated, multi-level model for this class of problematic pro-organizational behaviours and their multi-level antecedents and consequences.…”
mentioning
confidence: 99%